(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Advent of Women in Indian Industry: Landmarks and Achievements Dr. Vidya Kant Shukla This paper proposes to focus on the challenges and achievements of women entrepreneurs in India. It arrives at the finding that they are coming up very brightly on almost achievements of women entrepreneurs have been incorporated to narrate success stories of women industrial leaders in India. Our country is witnessing break-down of shackles by which women were enchained by far. Hence, it can be said that the future of women entrepreneurs is very bright and there is no denying that industrial world would see more women miracles and landmarks being achieved in coming days. We have firm faith in the age: Ability thy name is woman not frailty the name is woman!